The SHARING-AJA Website for Adolescent Reproductive Health Knowledge Levels - Niko Dima Kristianingrum; Ayut Merdikawati Merdikawati; Muladefi Choiriyah Choiriyah; Annisa Wuri Kartika (Universitas Aisyah Pringsewu, 2022)
Risk of sexual behaviour, abortion, and early marriage are the most common reproductive health problems in adolescents. Prevention strategies with digital technology are considered effective and appropriate by the development of adolescents. The aim of this study to analyze the use of SHARING AJA (Sadari keseHAtan ReproduksI saNG remaJA) media as an online educational media for the promotion of reproductive health. The study was Quasi-experimental with one group design approach (pre-post-test) in 26 respondents selected by consecutive sampling. Inclusion criteria are unmarried, have internet access via smartphone or laptop and are willing to be research respondents. The intervention was in the form of access to SHARING AJA for four weeks. The research instrument used a pre-test and post-test questionnaire. Data analysis using paired t-test. Results showed there is a significant difference between the knowledge of adolescents after being given intervention with a p-value of 0.001. The majority of respondents are satisfied with the use of the website with the highest average satisfaction on the ease of learning about reproductive health anytime and anywhere with a mean value of 4.27 ± 0.92. Conclusions was socialization and integration of the SHARING AJA website for the learning process and youth health development program in schools in collaboration with schools and public health centers. Abstrak: Masalah kesehatan reproduksi pada remaja meliputi perilaku seks berisiko, aborsi, dan pernikahan dini merupakan masalah yang paling sering terjadi. Strategi pencegahan berupa upaya promosi kesehatan dengan teknologi digital dinilai efektif dan tepat sesuai dengan tumbuh kembang remaja. Tujuan penelitian untuk menganalisis penggunaan media SHARING AJA (Sadari keseHAtan ReproduksI saNG remaJA) sebagai media edukasi online untuk promosi kesehatan reproduksi. Metode penelitian adalah Quasi eksperimental dengan pendekatan one group design (pre-posttest) pada 26 responden dipilih dengan consecutive sampling. Kriteria inklusi belum menikah, memiliki akses intrenet melalui smartphone atau laptop dan bersedia menjadi responden penelitian. Intervensi berupa akses ke SHARING AJA selama empat minggu. Instrumen penelitian menggunakan kuesioner pretest dan post-test. Analisa data menggunakan Uji paired t-test. Hasil didapatkan perbedaan yang signifikan antara pengetahuan remaja setelah diberikan intervensi dengan p-value 0,001. Mayoritas responden puas terhadap penggunaan website dengan rerata kepuasan tertinggi pada kemudahan untuk untuk mempelajari tentang kesehatan reproduksi kapan saja dan dimana pun berada dengan nilai rerata 4,27 ± 0,92. Kesimpulan yaitu sosialisasi dan integrasi website SHARING AJA untuk proses pembelajaran dan program pembinaan Kesehatan remaja di sekolah dengan kolaborasi bersama sekolah dan Puskesmas Wilayah